Patterns of Microbiome Composition Vary Across Spatial Scales in a Specialist Insect - Paddock, Kyle J.; Finke, Deborah L.; Kim, Kyung Seok; Sappington, Thomas W.; Hibbard, Bruce E. (Frontiers in Microbiology, 2022)
Microbial communities associated with animals vary based on both intrinsic and extrinsic factors. Of many possible determinants affecting microbiome composition, host phylogeny, host diet, and local environment are the most important. How these factors interact across spatial scales is not well understood. Here we seek to identify the main influences on microbiome composition in a specialist insect, the western corn rootworm (WCR; Diabrotica virgifera virgifera), by analyzing the bacterial communities of adults collected from their obligate host plant, corn (Zea mays), across several geographic locations and comparing the patterns in communities to its congeneric species, the northern corn rootworm (NCR; D. barberi). We found that bacterial communities of WCR and NCR shared a portion of their bacterial communities even when collected from disparate locations. However, within each species, the location of collection significantly influenced the composition of their microbiome. Correlations of geographic distance between sites with WCR bacterial community composition revealed different patterns at different spatial scales. Community similarity decreased with increased geographic distance at smaller spatial scales (~25 km between nearest sites). At broad spatial scales (>200 km), community composition was not correlated with distances between sites, but instead reflected the historical invasion path of WCR across the United States. These results suggest bacterial communities are structured directly by dispersal dynamics at small, regional spatial scales, while landscape-level genetic or environmental differences may drive community composition across broad spatial scales in this specialist insect.